Development of A Critical Learning Model to Enhance Students' Critical Thinking Skills in Biology Education - Muhammad Isrul; Ajeng Klarica Todingan; Agista Aprilian Pailang; Arsad Bahri; Muhammad Anwar Cece (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
The critical learning model is a learning model based on social constructivism. This study aims to develop a valid, practical, and effective learning model to improve students' critical thinking skills. The basis for the development of this learning model is that students are not actively involved in the PBL model because the problems are not relevant to students' lives, so the researcher developed a critical learning model that emphasizes the implementation of problems presented relevant to students' lives. This study uses the RnD research method, which refers to the ADDIE model. The research respondents included 2 expert validators, practitioners, and students of SMAN 9 Makassar. The development of the model produced a critical learning model syntax consisting of managing; directing; guiding and probing; explaining; and assessing; with purposive sampling at SMAN 9 Makassar class XII 5 Biology Interest. The results showed that the learning model met the validity criteria with a very high category (0.85), practicality with a practical category (83.98%), and effectiveness with a moderate category (0.67) so that the critical learning model is valid, practical, and effective in improving students' critical thinking skills. The results of field trials have proven that they can improve students' critical thinking skills.